The genetic profile of elite youth soccer players and its association with power and speed depends on maturity status - Murtagh, C. F.; Brownlee, T. E.; Rienzi, E.; Roquero, S.; Moreno, S.; Huertas, G.; Lugioratto, G.; Baumert, P.; Turner, D. C.; Lee, D.; Dickinson, P.; Lyon, K. A.; et al. (PLOS ONE, 2020)
We investigated the association of multiple single nucleotide polymorphisms (SNPs) with athlete status and power/speed performance in elite male youth soccer players (ESP) and control participants (CON) at different stages of maturity. ESP (n = 535; aged 8-23 years) and CON (n = 151; aged 9-26 years) were genotyped for 10 SNPs and grouped according to years from predicted peak-height-velocity (PHV), i.e. pre- or post-PHV, to determine maturity status. Participants performed bilateral vertical countermovement jumps, bilateral horizontal-forward countermovement jumps, 20m sprints and modified 505-agility tests. Compared to CON, pre-PHV ESP demonstrated a higher ACTN3 (rs1815739) XX (`endurance`) genotype frequency distribution, while post-PHV ESP revealed a higher frequency distribution of the PPARA (rs4253778) C-allele, AGT (rs699) GG genotype and NOS3 (rs2070744) T-allele (`power` genotypes/alleles). BDNF (rs6265) CC, COL5A1 (rs12722) CC and NOS3 TT homozygotes sprinted quicker than A-allele carriers, CT heterozygotes and CC homozygotes, respectively. COL2A1 (rs2070739) CC and AMPD1 (rs17602729) GG homozygotes sprinted faster than their respective minor allele carrier counterparts in CON and pre-PHV ESP, respectively. BDNF CC homozygotes jumped further than T-allele carriers, while ESP COL5A1 CC homozygotes jumped higher than TT homozygotes. To conclude, we have shown for the first time that pre- and post-PHV ESP have distinct genetic profiles, with pre-PHV ESP more suited for endurance, and post-PHV ESP for power and speed (the latter phenotypes being crucial attributes for post-PHV ESP). We have also demonstrated that power, acceleration and sprint performance were associated with five SNPs, both individually and in combination, possibly by influencing muscle size and neuromuscular activation.